Large-scale distributed computing and applications : models and trends - Cristea, Valentin. (Information Science Reference, 2010)
"The book has three overall objectives: offer a coherent and realistic image of today's research results in large scale distributed systems; explain state-of-the-art technological solutions for the main issues regarding large scale distributed systems; and presents the benefits of using large scale distributed systems and the development process of scientific and commercial distributed applications"--Provided by publisher.